Using Crossword Puzzles for The Eleventh-Grade Students in Teaching Vocabulary at Vocational High School - Nanda Nailatul Muna; Atik Rokhayani; Slamet Utomo (SIMPLE: International Journal of English Education, 2025)
Learning vocabulary is a continuous process in learning English that helps students improve their language ability to communicate. Lack of vocabulary causes the students difficulties expressing their ideas and understanding in learning English. The researcher used a Crossword Puzzle as a medium for teaching vocabulary to encourage the students’ interest in vocabulary learning. The purpose of the study was to determine the effectiveness of the Crossword Puzzle for the eleventh-grade students in teaching vocabulary at Vocational High School. The method of the study was quantitative and used a pre-experimental design with one group pre-test and post-test. The researcher chose one class of the eleventh-grade students as a sample for this study. The results of this study showed that the mean pre-test score was 67.43, while the mean of post-test scores was 86.14. Hypothesis testing used the Wilcoxon Signed Ranks Test showed the value Sig. (2-tailed) of 0.00 < 0.05. It is indicated that there is an improvement using the Crossword Puzzles for the eleventh-grade students in teaching vocabulary at Vocational High School.